Andean truths : transitional justice, ethnicity, and cultural production in post-shining path Peru - Lambright, Anne (Liverpool Latin American studies, 2015)
Studies the way in which literature, drama, film, and the visual arts contest the dominant narrative of national peace and reconciliation, as constructed by Peru's Truth and Reconciliation Commission.